Investigation of Impact Properties of Composite from Seashell & Carbon Fiber Using Simulation - DEVADASON, DILWWYN ANAND; MOHAMED HATTA, MOHAMED NASRUL (Research Progress in Mechanical and Manufacturing Engineering, 2022)
This research is based on simulation using the Explicit Dynamic method from Abaqus CAE software. The focus of this research is to investigate the impact properties of composite from seashell waste and carbon fibre. Five models are designed, each of it with the same dimension and parameters but the global seed size is modified (0.4mm, 0.6mm, 0.8mm, 1.0mm, 1.2mm). This was done to show the relationship between mesh sensitivity of sample and accuracy of impact properties. The kinetic energy and strain energy of the seashell composite plate was obtained as a result from the simulation. The kinetic energy on smaller mesh size (0.4mm) was higher at 402844J and almost similar for the 0.6mm, 0.8mm and 1.0mm mesh sizes compared to the largest mesh size (1.2mm) which had a lower value of 402838J. Apart from that, the strain energy on the four smaller mesh size( 0.4mm-1.0mm) had lower energy value ranging from 4.89343J to 5.31961J compared to the largest mesh size which showed significantly larger energy value of 16.4741J. The Von Mises stress from the smallest mesh size to the largest showed a linearly decreasing graph. In addition to that, the fracture and deformation of the seashell composite plate was also analysed. The plate with the largest mesh size (1.2mm) failed to crack when subjected to impact load. The endpoint fracture of the plate with smallest mesh size showed wider area of failure compared to plate with the largest mesh size which only deformed.